1981
DOI: 10.1182/blood.v57.2.298.298
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of the in vivo role of erythropoietin or companion molecules induced by hypoxia on proliferation and continuing differentiation of BFU-e in PCDC

Abstract: Normal and plethoric bone marrow cells were grown in plasma clot diffusion chambers (PCDC) implanted into the peritoneum of normal mice or mice submitted to 7 her of hypoxia (23,000 ft) daily, on a single day or on 2 consecutive days at different times after implantation of the PCDC's. Daily discontinuous hypoxia (DDH) produced more 6-day bursts than other treatments. Hypoxia on days 1 and 2 after implantation was nearly as effective as DDH on day-6 bursts. Later bouts of hypoxia or a singly hypoxic exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Activity produced by antigen-or Schistosomu munsoni-stimulated lymphoid cells [97,98] seems to be a good source of an eosinophilopoietic factor. Erythropoietin, the physiological regulator of in vivo erythropoiesis, also enhances erythroid cell production in DCs [13, 30,36,871. Assessment of conditioned media from neoplastic cell line cultures has revealed that cells with T [24,50] and B cell [49] characteristics elaborate activities which stimulate CFUd.…”
Section: Humoml Effectsmentioning
confidence: 99%
“…Activity produced by antigen-or Schistosomu munsoni-stimulated lymphoid cells [97,98] seems to be a good source of an eosinophilopoietic factor. Erythropoietin, the physiological regulator of in vivo erythropoiesis, also enhances erythroid cell production in DCs [13, 30,36,871. Assessment of conditioned media from neoplastic cell line cultures has revealed that cells with T [24,50] and B cell [49] characteristics elaborate activities which stimulate CFUd.…”
Section: Humoml Effectsmentioning
confidence: 99%